Experimental assessment of an RFID-based crack sensor for steel structures. (24th July 2017) - Martínez-Castro, R E; Jang, S; Nicholas, J; Bansal, R
Abstract: The use of welded steel cover plates had been a common design practice to increase beam section capacity in regions of high moment for decades. Many steel girder bridges with cover plates are still in service. Steel girder bridges are subject to cyclic loading, which can initiate crack formation at the toe of the weld and reduce beam capacity. Thus, timely detection of fatigue cracks is of utmost importance in steel girder bridge monitoring. To date, crack monitoring methods using in-house radio frequency identification (RFID)-based sensors have been developed to complement visual inspection and provide quantitative information of damage level. Offering similar properties at a reduced cost, commercial ultra-high frequency (UHF) passive RFID tags have been identified as a more financially viable option for pervasive crack monitoring using a dense array of sensors. This paper presents a study on damage sensitivity of low-cost commercial UHF RFID tags for crack detection and monitoring on metallic structures. Using backscatter power as a parameter for damage identification, a crack sensing system has been developed for single and multiple tag configurations for increased sensing pervasiveness. The effect on backscatter power of the existence and stage of crack propagation has been successfully characterized. For further automation of crack detection, a damage index based on the variation of backscatter power has also been established. The tested commercial RFID-based crack sensor contributes to the usage of this technology on steel girder bridges.